Pemikiran Politik Islam dan Modern - Khoirul Huda; Andre Selamat Sinaga; Dinda Ratulangi (Pusat Riset dan Inovasi Nasional, 2024)
The development of Islamic political thought cannot be separated from the historical context and social dynamics surrounding it. One significant period that influenced the direction of this thought is the era of Western colonialism in the 19th to early 20th centuries. During this period, much of the Islamic world was under Western colonial rule, which had a profound impact on the social, political, and intellectual conditions of Muslims. Within the Muslim community itself, various internal issues related to religious understanding arose, causing difficulties in facing the dominance and hegemony of the West. Islamic political thought became one of the fields of study in political science, which is not only relevant today but also gained attention during the classical Islamic period. This study is highly significant, both in the development of knowledge and as a framework for political practice. Therefore, it is important to study Islamic political thought, as it provides deep insights into political dynamics and Islam’s contribution to shaping existing political systems, as well as offering perspectives that are useful in facing contemporary global challenges.